Programmed ventricular stimulation predicts arrhythmic events and survival in hypertrophic cardiomyopathy. (1st March 2018) - Gatzoulis, Konstantinos A.; Georgopoulos, Stavros; Antoniou, Christos-Konstantinos; Anastasakis, Aris; Dilaveris, Polychronis; Arsenos, Petros; Sideris, Skevos; Tsiachris, Dimitris; Archontakis, Stefanos; Sotiropoulos, Elias; Theopistou, Artemisia; Skiadas, Ioannis; et al.
Abstract: Background: Sudden cardiac death (SCD) risk stratification in hypertrophic cardiomyopathy (HCM) in the context of primary prevention remains suboptimal. The purpose of this study was to examine the additional contribution of programmed ventricular stimulation (PVS) on established risk assessment. Methods: Two-hundred-and-three consecutive patients with diagnosed HCM and ≥ 1 noninvasive risk factors were prospectively enrolled over 19 years. Patients were risk stratified, submitted to PVS and received an implantable cardioverter-defibrillator (ICD) according to then-current American Heart Association (AHA) guidelines and inducibility. Participants were prospectively followed-up for primary endpoint occurrence (appropriate ICD therapy or SCD). Contemporary (2015) AHA and European Society of Cardiology (ESC) guidelines were retrospectively assessed. Results: During a median follow-up period of 60 months the primary endpoint occurred in 20 patients, 19 of whom were inducible and received an ICD. Overall, 79 patients (38.9%) were inducible and 92 patients (45.3%) received an ICD (PVS sensitivity = 95%, specificity = 67.2%, positive predictive value = 24%, negative predictive value = 99.2%). AHA and ESC guidelines application misclassified 3 and 9 primary endpoint-meeting patients, respectively. Inducibility was the most important determinant of event-free survival in multivariate Cox regression (hazard ratio = 33.3). A combined approach of ESC score ≥ 6% or AHA indication for ICD with PVS inducibility yielded absolute sensitivity and negative predictive value, the former at a more cost-effective and specific way. Conclusions: Inducibility at PVS predicts SCD or appropriate device therapy in HCM. Non-inducibility is associated with prolonged event-free survival, while the procedure was proven safe. Reintegration of PVS into established risk stratification models in HCM may improve patient assessment.